ANALISIS EFEKTIVITAS PENGGUNAAN SISTEM SAP DALAM PENGELOLAAN GUDANG DI PT GIVAUDAN INDONESIA DEPOK - Faridah, Faridah; Yoeliastuti, Yoeliastuti (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effectiveness of the use of the System Application and Product in Data Processing (SAP) in warehouse management at PT Givaudan Indonesia, Depok. The main issue addressed is the discrepancy between system-recorded stock data and physical inventory, which is caused by human factors and technical constraints. The research employs a descriptive qualitative method supported by quantitative data obtained from questionnaires distributed to 12 warehouse operational respondents. The results indicate that the implementation of SAP at PT Givaudan Indonesia, Depok, is categorized as highly effective, with an average score of 4.31 out of 5.00. The primary strengths of the system are its support for the First Expired First Out (FEFO) principle (4.42) and the speed of data input (4.42). However, this effectiveness is still hindered by operator discipline in scanning activities (3.75) as well as network and system stability issues (3.75).